A second KRT71 allele in curly coated dogs. (15th November 2018) - Bauer, A.; Hadji Rasouliha, S.; Brunner, M. T.; Jagannathan, V.; Bucher, I.; Bannoehr, J.; Varjonen, K.; Bond, R.; Bergvall, K.; Welle, M. M.; Roosje, P.; Leeb, T.
Summary: Major characteristics of coat variation in dogs can be explained by variants in only a few genes. Until now, only one missense variant in the KRT71 gene, p.Arg151Trp, has been reported to cause curly hair in dogs. However, this variant does not explain the curly coat in all breeds as the mutant 151 Trp allele, for example, is absent in Curly Coated Retrievers. We sequenced the genome of a Curly Coated Retriever at 22× coverage and searched for variants in the KRT71 gene. Only one protein‐changing variant was present in a homozygous state in the Curly Coated Retriever and absent or present in a heterozygous state in 221 control dogs from different dog breeds. This variant, NM_001197029.1:c.1266_1273delinsACA, was an indel variant in exon 7 that caused a frameshift and an altered and probably extended C‐terminus of the KRT71 protein NP_001183958.1:p.(Ser422ArgfsTer?). Using Sanger sequencing, we found that the variant was fixed in a cohort of 125 Curly Coated Retrievers and segregating in five of 14 additionally tested breeds with a curly or wavy coat. KRT71 variants cause curly hair in humans, mice, rats, cats and dogs. Specific KRT71 variants were further shown to cause alopecia. Based on this knowledge from other species and the predicted molecular consequence of the newly identified canine KRT71 variant, it is a compelling candidate causing a second curly hair allele in dogs. It might cause a slightly different coat phenotype than the previously published p.Arg151Trp variant and could potentially be associated with follicular dysplasia in dogs.